Wacana kartun editorial berbahasa Melayu: Satu kajian pragmatik / Mat Zaid Hussein - Mat Zaid , Hussein (2016)
This study which was conducted based on the theory of pragmatics aims to analyze the discourse of Malay editorial cartoons. The qualitative study which is descriptive in nature examines aspects of the discourse which followed and aspects which flouted the cooperative principle in conversation. Language use in the discourse of editorial cartoons in Malay is also examined. The theoretical framework for this study is Grice’s (1975) Cooperative Principle. The Cooperative Principle and its conversational maxims, i.e. maxim of quantity, maxim of quality, maxim of relation or relevance, and maxim of manner were used for data analysis. Data for the study are editorial cartoons in Malay which were published in newspapers such as Berita Minggu, Mingguan Malaysia and Harian Metro between 2006 and 2008. It is a fact that underlying the delivery of a message or criticism laced with humor, the discourse of editorial cartoons often flouts the cooperative principles which ought to be followed in conversation. Contrary to the approach of communication that is bona fide or reasonable and responsible, the discourse of the analyzed editorial cartoons appears to result from a process of communication that occurred in a non-bona fide manner. The analysis of utterances or conversations in the discourse of the editorial cartoons revealed that speakers often, either intentionally or unintentionally, violated the Cooperative Principle in conversation. Pragmatically, the violations gave rise to certain effects or implications on the meanings behind the speakers’ utterances. This shows that the meanings contained in the conversations in editorial cartoons are not direct or conceptual per se but rather are indirect, covert or implied. Therefore, in delivering the editorial cartoon discourse, the cartoonists, either with consideration of lingual or extra-lingual factors, have symbolically produced non-bona fide discourse that deviate from the expected Cooperative Principle and conversation maxims to produce conversational implicatures. The examination of conversational implicatures that exist in the discourse of Malay editorial cartoons showed that they resulted from the existence of inconsistencies or contradictions in conventional norms within reasonable or bona fide conversations. The inconsistencies or contradictions that occurred led to the violations of the Cooperative Principle and maxims of conversation in the Malay editorial cartoon discourse. The conversational implicatures that exist produced meanings or messages which are implicit or hidden. The analysis of the conversational implicatures in this study is based on pragmatic approaches to reveal the true meaning being delivered and the pragmatic inference that exists and relates to the meaning that lies behind the issue or message conveyed in the discourse of Malay editorial cartoons. The pragmatic approach employed in this study is found to be effective in interpreting and dealing with problems associated with utterances and conversations containing implicit and hidden meanings in the discourse of editorial cartoons that were studied. The analysis found that Malay editorial cartoons which contain conversational implicatures occurred due to violations of conversational maxims, i.e. maxim of quantity, maxim of quality, maxim of relation or relevance, and maxim of manner. The study also focused its analysis on the methods and forms of language use in the discourse of editorial cartoons in Malay. The utilization of various elements and forms of verbal language such as lexical and grammatical ambiguities, figurative language or figurative forms which include metaphors, analogy, personifications, elements of irony, deixis and idiomatic meanings was analyzed. Apparently, all the elements and forms of the verbal language which were examined showed implicit meanings or conversational implicatures in the discourse of the editorial cartoons.